A Porter-SCOR modelling approach for the hospital supply chain. Issue 3 (13th January 2009) - Di Martinelly, Christine; Riane, Fouad; Guinet, Alain
We suggest in this paper a modelling approach that extends the Analysis Specification Conception and Implementation (ASCI) methodology by putting the accent on the performance dimension. We suggest a value model as an extension of ASCI methodology based on Porter's and SCOR models. We underline the necessity of defining an appropriate system of performance metrics that should be defined in accordance with the hospital value system. This extended methodology provides the user with a better understanding of the way the system works and enables to document practices and processes.